Printed aerogels: chemistry, processing, and applications - Feng, Junzong; Su, Bao-Lian; Xia, Hesheng; Zhao, Shanyu; Gao, Chao; Wang, Lukai; Ogbeide, Osarenkhoe; Feng, Jian; Hasan, Tawfique (Chemical Society reviews, 2021)
As an extraordinarily lightweight and porous functional nanomaterial family, aerogels have attracted considerable interest in academia and industry in recent decades. Despite the application scopes, the modest mechanical durability of aerogels makes their processing and operation challenging, in particular, for situations demanding intricate physical structures. "Bottom-up" additive manufacturing technology has the potential to address this drawback. Indeed, since the first report of 3D printed aerogels in 2015, a new interdisciplinary research area combining aerogel and printing technology has emerged to push the boundaries of structure and performance, further broadening their application scope. This review summarizes the state-of-the-art of printed aerogels and presents a comprehensive view of their developments in the past 5 years, and highlights the key near- and mid-term challenges.